1993
DOI: 10.1037/0735-7044.107.3.493
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the opioid and nonopioid hypoalgesic systems at the level of the brainstem and spinal cord: Does a coulometric relation predict the emergence or form of environmentally induced hypoalgesia?

Abstract: Prior research suggests that a coulometric relation (Intensity x Duration) determines whether an opioid or nonopioid hypoalgesic system is activated by afferent nociceptive information. Using a paradigm that generates a brainstem-mediated hypoalgesia on the tail-flick test, we found that a coulometric relation does not predict either the emergence or the form of shock-induced hypoalgesia in decerebrate rats. In fact, no evidence was obtained that the brainstem's opioid hypoalgesic system can be activated by as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(88 citation statements)
references
References 34 publications
(95 reference statements)
7
81
0
Order By: Relevance
“…Separate groups received nothing (0 s) or 30 min of uncontrollable, intermittent tailshock. The shocks were 1.5 mA, 0.08 s in duration, and occurred on a variable time schedule (range 0.2 to 3.8 s) with a mean interstimulus interval of 2.0 s. (Shock at an intensity of 1.5 mA [AC, constant current] is known to engage antinociceptive mechanisms within the spinal cord [18,19], vigorous defensive behavior in intact rats, and pain in humans [see 8,9].) An experimenter blind to the subject's drug treatment recorded whether the shocked rats vocalized during the first minute of stimulation.…”
Section: Shock Treatmentsmentioning
confidence: 99%
“…Separate groups received nothing (0 s) or 30 min of uncontrollable, intermittent tailshock. The shocks were 1.5 mA, 0.08 s in duration, and occurred on a variable time schedule (range 0.2 to 3.8 s) with a mean interstimulus interval of 2.0 s. (Shock at an intensity of 1.5 mA [AC, constant current] is known to engage antinociceptive mechanisms within the spinal cord [18,19], vigorous defensive behavior in intact rats, and pain in humans [see 8,9].) An experimenter blind to the subject's drug treatment recorded whether the shocked rats vocalized during the first minute of stimulation.…”
Section: Shock Treatmentsmentioning
confidence: 99%
“…As Millan (2002) points out in his extensive review of the descending control of pain, the difference in the mechanisms of facilitation and inhibition of nociception are primarily in receptor subtypes coupled to differing intracellular mechanisms. Spinal pathways, through mechanisms elaborated from the gate-control theory, and supraspinal descending inhibitory pain pathways, both play a role in mediating SIA (Grau, 1987;Grau et al, 1990;Madden et al, 1977;Meagher et al, 1993;Meagher et al, 1990;Rhudy et al, 2004;. Nociceptive information is then relayed either directly to the cortex or indirectly to the cortex through the brainstem, midbrain, and thalamus via the ascending pain pathways (for review see Millan, 1999).…”
Section: Neural Substrates Involved In Siamentioning
confidence: 99%
“…Prior parametric studies have shown that these three modes of defense can be sequentially engaged by increasing shock severity (duration, intensity, and/or density; Fanselow and Lester 1988;Meagher et al in review), and rely on distinct neural systems (Meagher et al 1993;Fanselow 1994;Grau et al 1996;Crown et al 2000). Following Fanselow (1994), we assumed that these distinct modes of defense can likewise be sequentially engaged by different levels of negative affect.…”
Section: Discussionmentioning
confidence: 98%